PENDAMPINGAN USAHA KECIL PENGOLAHAN KUE DI KECAMATAN TLANAKAN, KABUPATEN PAMEKASAN - Laili Amalia; Yuliarsih Yuliarsih; Rohmah Indahwati; Irwan Darmawan (COVIT (Community Service of Health), 2022)
Three small businesses, Andre Bakery, Handyani, and Arlin Bakery, located in Tlanakan village, Tlanakan sub-district, kab. Pakistan. Considering that the heads of families from each partner work as construction workers, the existence of these three companies is absolutely necessary because they can meet the needs of this simple family. However, it is very unfortunate lately, due to the Covid-19 pandemic, partner income has decreased drastically, reaching 30–50%. Partner issues will be handled with an approach that combines intensive counseling with the transfer of knowledge and technology, which includes good manufacturing practice (GMP) training, food safety counseling, product halal counseling, strengthening business management through P-IRT registration and halal products, product packaging improvements. , and the provision of production support facilities. This activity is beneficial for the three partners. The results of this PKM activity include the publication of activities in the form of improving partner production facilities, implementing partner technical guidance, and scientific articles on PKM service activities. It is very important to offer partner support intensely. Keywords: Mentoring, Small Business